The relationship between housing prices and transport improvements : a comparison of metropolitan and rural areas in a large but thinly populated European country - Vífill Karlsson 1965- (2008)
Vinnugrein / Working paper In this paper, I examine the relationship between housing prices and transport improvements. Due to the general consumer preference for access over amenity value, there is a relationship between distance and house prices. Thus, it is reasonable to believe that transportation improvements tend to influence house prices. It has been documented that the relationship between distance and house prices is negative for a densely populated area with one central business district (CBD). I will examine whether this relationship holds for a thinly populated area with one CBD, and will test whether this relationship is marginally different between locations. A macro panel data set from Iceland will be used. It provides several essential variables for 19 counties in Iceland from 1981 through 2005. Samband fasteignaverðs og samgöngubóta er rannsakað í þessari tímaritsgrein. Vild neytenda er undirliggjandi þáttur fyrir því að fjarlægð hefur áhrif á fasteignaverð. Þess vegna er ástæða til þess að gera ráð fyrir að samgöngubætur hafi bein áhrif á fasteignaverð. Það hefur oft verið sýnt fram á að samband fasteignaverðs og fjarlægðar fasteigna frá borgarmiðju er neikvætt í þéttbýlum samfélögum með einum borgarkjarna. Í þessari rannsókn verður kannað hvort þetta samband sé til staðar í strjálbýlum samfélögum og það sé breytilegt frá einum stað til annars. Makró panel gögn frá Ísland sem ná yfir nokkrar lykilþætti fasteignamarkaðarins verða nýtt í rannsókninni. Þar er Íslandi skipt upp í 19 sýslur á tímabilinu 1981 til 2005.